2018
DOI: 10.1016/j.cmet.2018.02.020
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Inhibiting HIF Asparaginyl Hydroxylase Regulates Oxidative Metabolism and Accelerates Metabolic Adaptation to Hypoxia

Abstract: SummaryAnimals require an immediate response to oxygen availability to allow rapid shifts between oxidative and glycolytic metabolism. These metabolic shifts are highly regulated by the HIF transcription factor. The factor inhibiting HIF (FIH) is an asparaginyl hydroxylase that controls HIF transcriptional activity in an oxygen-dependent manner. We show here that FIH loss increases oxidative metabolism, while also increasing glycolytic capacity, and that this gives rise to an increase in oxygen consumption. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 65 publications
5
63
0
Order By: Relevance
“…Interestingly, among the accumulated substrates, succinate and fumarate could also contribute to HIF stability [ 165 ]. The recent study confirms this opinion that the FIH in concert with PHD/VHL in rapidly response to hypoxia, in turn, altered metabolites lead to HIF stability [ 56 ]. And authentic study speculated that lipopolysaccharide produced by gram-negative bacteria potently enhance the TCA-cycle intermediate metabolites succinate, performing a role of stabilizing HIF-1α accompanied with increased interleukin-1β, which finally mediating inflammation [ 161 ].…”
Section: Influence Of Intracellular Metabolites On Hif-α Stability Thsupporting
confidence: 54%
See 2 more Smart Citations
“…Interestingly, among the accumulated substrates, succinate and fumarate could also contribute to HIF stability [ 165 ]. The recent study confirms this opinion that the FIH in concert with PHD/VHL in rapidly response to hypoxia, in turn, altered metabolites lead to HIF stability [ 56 ]. And authentic study speculated that lipopolysaccharide produced by gram-negative bacteria potently enhance the TCA-cycle intermediate metabolites succinate, performing a role of stabilizing HIF-1α accompanied with increased interleukin-1β, which finally mediating inflammation [ 161 ].…”
Section: Influence Of Intracellular Metabolites On Hif-α Stability Thsupporting
confidence: 54%
“…In addition, under normoxia, an asparagine residue in the C-terminal activation domain of HIF-1α and HIF-2α is hydroxylated by factor inhibiting HIF (FIH), resulting in the inability of the region to bind to p300, thus weakening the activation of the HIF pathway. However, in hypoxia, due to the inactivation of FIH, HIF-1α and HIF-2α avoid being hydroxylated, and subsequently translocate into the nucleus to bind with ARNT and p300, leading to the activation of HIF target genes [ 56 ]. The effect of FIH on the HIF-α further deepens our understanding of the mechanisms governing the stability of HIF-α.…”
Section: Canonical and Non-canonical Regulation Of Hif Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia-inducible factor 1 (HIF1) is a major transcription factor that induces metabolic reprogramming via upregulation of anaerobic glycolysis and downregulation of oxidative phosphorylation 20,30 . HIF1 is activated through strict control of its alpha subunit (HIF1α) by transcription, translation, posttranslational modification like prolyl-or asparaginyl hydroxylation and ubiquitination, and microtubule-associated nuclear transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been suggested that HIF1α plays an important role in the HIF1-regulated metabolism. In fact, stabilizing HIF1α through loss of the factor inhibiting HIF (FIH) or through the oxidative dimerization of the prolyl hydroxylase domain protein 2 (PHD2) facilitates metabolic adaptation to hypoxia 30,35 . Previous studies showed that HIF1αoverexpressed MSC exhibits high immunomodulatory effects and high resistance to hypoxia-induced apoptosis 36,37 .…”
Section: Introductionmentioning
confidence: 99%